(1487) The two - level planning model نموذج التخطيط ذو المستويين - Hamza, Abd-El-Kader; El Daoushy, Abdalla (The Institute of National Planning, 2018)
Economic planning is a task that can be approached by different method and idea. As an example by the use of input-output tabie. But such input—output tables are not suited for optimiziation and is mereiy designed to achieve correct proportions between sectors.